Behavioral defects and downregulation of hippocampal BDNF and nNOS expression in db/db mice did not improved by chronic TGF-β2 treatment - Tomiga, Yuki; Higaki, Yasuki; Anzai, Keizo; Takahashi, Hirokazu (Frontiers in Physiology, 2022)
Epidemiological evidence suggests that there is a link between diabetes and mood disorders, such as depression and anxiety. Although peripheral or central inflammation may explain this link, the molecular mechanisms are not fully understood and few effective treatments for diabetes or mood disorders are available. In the present study, we aimed to determine whether transforming growth factor (TGF)-β2, an anti-inflammatory substance, might represent a potential therapeutic agent for diabetes-related mood behaviors. TGF-β2 expression in the hippocampus is affected by anxiolytic drugs and stress exposure, it is able to cross the blood-brain barrier, and it is as an exercise-induced physiological adipokine that regulates glucose homeostasis. Therefore, we hypothesized that a chronic TGF-β2 infusion would ameliorate diabetes-related glucose intolerance and mood dysregulation. To determine the effects of the chronic administration of TGF-β2 on diabetes, we implanted osmotic pumps containing TGF-β2 into type 2 diabetic mice (db/db mice), and age-matched non-diabetic control (WT) mice and db/db mice were infused with vehicle (PBS), for 12 consecutive days. To assess anxiety-like behaviors and glucose homeostasis, the mice underwent elevated plus maze testing and intraperitoneal glucose tolerance testing. Hippocampal and perigonadal visceral white adipose tissue (pgWAT) samples were obtained 12 days later. Contrary to our hypothesis, TGF-β2 infusion had no effect on diabetes-related glucose intolerance or diabetes-related behavioral defects, such as inactivity. In db/db mice, the expression of inflammatory markers was high in pgWAT, but not in the hippocampus, and the former was ameliorated by TGF-β2 infusion. The expression of brain-derived neurotrophic factor and neuronal nitric oxide synthase, important regulators of anxiety-like behaviors, was low in db/db mice, but TGF-β2 infusion did not affect their expression. We conclude that although TGF-β2 reduces the expression of pro-inflammatory markers in the adipose tissue of diabetic mice, it does not ameliorate their obesity or mood dysregulation.